Everyday executive function and adaptive skills in children and adolescents with autism spectrum disorder: Cross-sectional developmental trajectories. (September 2018) - Kouklari, Evangelia-Chrysanthi; Tsermentseli, Stella; Monks, Claire P
Background and aims: The development of Executive Function in Autism Spectrum Disorder has been investigated using mainly performance-based executive function measures. Less is known about the development of everyday executive function skills. The present study aimed to identify the developmental patterns of everyday executive function of children and adolescents with autism spectrum disorder compared to neurotypical controls. The association between executive function and adaptive skills was also investigated. Methods: The present study used a cross-sectional developmental trajectory approach and data were collected from 57 children and adolescents with autism spectrum disorder, matched to 63 controls of the same age (7–15 years). Results: Results showed age-related performance declines in most everyday executive function domains (e.g. inhibition, working memory, planning) in autism spectrum disorder, whereas for executive function emotional control and shift, non-significant differences emerged across age in autism spectrum disorder. Everyday executive function predicted adaptive skills over and above age and IQ, in participants overall. Conclusions and implications: These results suggest that several everyday executive function problems increase in adolescence in autism spectrum disorder and that these everyday executive function developmental patterns deviate to a great extent from those of typical development. Shedding more light on the developmental course of all types of executive function processes as well as their association with crucial social outcomes in autism spectrum disorder could contribute to a better theoretical understanding of the heterogeneity of the neurocognitive development in autism spectrum disorder.